Implementation of Full Day School Based on Islamic culture for strengthening The Religious Character of Students in Matsasurba Malang - Nurul Sidrah; M. Mansur (Jurnal Civic Hukum, 2019)
ABSTRACTThe purpose of this research is to find out and describe (1) the concept and implementation of full day school based on Islamic culture for strengthening religious character of students at the Islamic Junior High School Surya Buana Malang (2) the inhibiting and supporting factors, (3) the solutions to deal with the inhibiting factors that emerging. This research method uses descriptive research with a qualitative approach, collecting data through observation, interviews, and documentation. Data were analyzed qualitatively, through stages of data collection, data reduction, data presentation, and data verification, along with data validity techniques using triangulation techniques. The result of this study showed that (1) the concept of full day school that applied is islamic full day school by focusing on strengthening the religious character of students. The implementationof full day school based on Islamic culture aims to make to make students have good character through the habituation that is carried out since students enter school until after school. (2) the inhibiting factors consist of diverse inputs, location and school regulations. Supporting factors consist of internal and external support. (3) the solutions to deal with the inhibiting factors that emerging is to provide special guidance, increase religious activities, comunnication and cooperation with parents of students.